Racial/Ethnic Inequities in Paid Parental Leave Access (Mary Ann Liebert, 2021)
Purpose: Severe racial inequities in maternal and infant health in the United States are caused by the many forms of systemic racism. One manifestation of systemic racism that has received little attention is access to paid parental leave. The aim of this article is to characterize racial/ethnic inequities in access to paid leave after the birth of a child. Methods: We analyzed data on women who were employed during pregnancy (n=908) from the Bay Area Parental Leave Study of Mothers, a survey of mothers who gave birth in the San Francisco Bay Area in 2016?2017. We examined differences in access to government- and employer-paid leave, the duration of leave taken, and the percent of usual pay received while on leave. To explore these differences, we further examined knowledge of paid leave benefits and sources of information. Results: Non-Hispanic (NH) black and Hispanic women had significantly less access to paid leave through their employers or through government programs than their NH white and Asian counterparts. Relative to white women, Asian, Hispanic, and black women received 0.9 (p<0.05), 2.0 (p<0.01), and 3.6 (p<0.01) fewer weeks, respectively, of full-pay equivalent pay during their parental leaves. Despite inequitable access to paid leave, the duration of parental leave taken did not differ by race/ethnicity. Conclusions: Inequitable access to paid parental leave through both employers and government programs exacerbates racial inequities at birth. This form of structural racism could be addressed by policies expanding access to paid leave.